Implementation of Omotenashi in Japanese Ryokan - Wahyu Nur Wijayanti; Akhmad Saifudin (Universitas Dian Nuswantoro, 2021)
Omotenashi, often referred to as Japanese hospitality, is a service to customers based on Japanese spirit and culture. Omotenashi is evident in the services provided by a ryokan, which is a traditional Japanese inn. This paper seeks to describe the application of omotenashi in ryokan management, how omotenashi control is implemented, and what the implementations are. The research was conducted by observing the involvement of the Hyoe Koyokaku ryokan, an old ryokan located in the tourist area of Arima Onsen. From the results of observations and analysis, it was found that ryokan employees control omotenashi as a vision of service to customers through training, instruction, and improvement based on feedback. The implementation of ometenashi is manifested in personalization, host-guest relationships, hospitableness, and lots of little surprises